An epidemiological study of malaria parasites among long–tailed macaques (Macaca fascicularis), pig–tailed macaques (Macaca nemestrina) and silver–leaf monkeys (Trachypithecus cristatus) in Sumatra Region, Indonesia - Sarwo Handayani; Rita Marleta Dewi; Lucia Dwi Antika; Novaria Sari Dewi Panjaitan (Asian Pacific Journal of Tropical Medicine, 2025)
Objective: To ascertain the prevalence and distribution of malaria parasites among the three monkeys species from three provinces in Sumatra Island, Indonesia. Methods: Infections with Plasmodium spp. were determined morphologically from the blood smears which were stained with Giemsa solution and molecularly through nested polymerase chain reaction (PCR) in DNA samples from 68 primates, which were captured at three locations: Jambi (Bungo district), Bengkulu (Muko-Muko district), and Riau Islands (Lingga district). Results: Out of 68 samples analyzed, 46 were positive for various Plasmodium species, including Plasmodium knowlesi, Plasmodium cynamolgi, Plasmodium inui, and Plasmodium coatneyi. Over one-third of the population exhibited multiple infections, with Plasmodium inui being the most predominant strain. Conclusions: The high prevalence of multiple malaria infections in monkeys, coupled with the rising reports of primate malaria cases in human raises questions about the potential for human transmission. These findings emphasize the necessity for ongoing monitoring and endeavors to comprehend and alleviate the risk of zoonotic malaria transmission, particularly in areas experiencing environmental changes.